The loculoascomycete species diversity of National Park “Oleshkivski Pisky” (Kherson region, Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The species composition of loculoascomycetes in the National Natural Park "Oleshkivski Pisky" has been studied. It includes 34 species from 18 genera, 10 families, 3 orders and group orders Incertae sedis, 2 subclasses of class Dothideomycetes. In the taxonomic structure of the investigated species composition it was established predominance of the subclass Pleosporomycetidae, of the order Pleosporales, of the family Leptosphaeriaceae, as well as genus Leptosphaeria. We analyzed the characteristics of habitat distribution of species in communities 4 types of vegetation. We have studied the ecological structure of mycobiota and consortial connections with 19 species of plants from 11 families. In the ecological structure it was established the dominance of saprotrophs. It was noted, that a variety of substrates equally favors the spread and herbotrophic and xylotrophic loculoascomycetes. Ecological features of the species relating to the stages of ontogeny, of habitat, and their distribution, were discussed.
Keywords: loculoascomycetes, species diversity, Oleshkivski Pisky.